Structure, electronic component device, and method for manufacturing structure

A resin member with a cured epoxy resin and nitrogen-containing phenol novolac resin improves adhesion to metal films, addressing electromagnetic interference in electronic devices by enhancing bonding strength and consistency.

CN119174002APending Publication Date: 2024-12-20RESONAC CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380037355.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-11-25
Filing Date
2023-11-21
Publication Date
2024-12-20

Smart Images

  • Figure BDA0005108726830000051
    Figure BDA0005108726830000051
  • Figure BDA0005108726830000131
    Figure BDA0005108726830000131
Patent Text Reader

Abstract

A structure including a resin member and a metal film disposed on a surface of the resin member, the resin member including a cured product of an epoxy resin and a curing agent, the curing agent including a nitrogen-containing phenol novolac resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a structure, an electronic component device, and a method for manufacturing the structure. Background Art

[0002] Resins such as epoxy resins are widely used as sealing materials for protecting the periphery of electronic components in electronic component devices such as semiconductor packages (for example, see Patent Document 1).

[0003] Patent Document 1: Japanese Patent Application Publication No. 2021-027315 Summary of the invention

[0004] Problems to be solved by the invention

[0005] As electronic devices have become smaller and more functional in recent years, the mounting density of electronic components in electronic component devices has increased. As a result, there has been a problem in which noise generated by electronic component devices causes electromagnetic interference with surrounding electronic devices.

[0006] As one of the methods for suppressing electromagnetic interference, there is a method of further covering the surface of a resin member disposed around an electronic component device with a metal film.

[0007] However, when the surface of a resin member disposed around an electronic component is covered with a metal film, the adhesion between the metal film and the resin member is evaluated under specific conditions. As a result, it is found that the evaluation result of the adhesion varies depending on the type of the resin member.

[0008] In view of the above situation, the subject of one embodiment of the present disclosure is to provide a structure having excellent adhesion between a resin component and a metal film disposed on its surface, and an electronic component device including the structure. The subject of another embodiment of the present disclosure is to provide a method for manufacturing a structure having excellent adhesion between a resin component and a metal film disposed on its surface.

[0009] Technical means of solving problems

[0010] Specific means for solving the above-mentioned problems include the following aspects.

[0011] <1> A structure including a resin member and a metal film disposed on a surface of the resin member, wherein the resin member includes a cured product of an epoxy resin and a curing agent, and the curing agent includes a nitrogen-containing phenol novolac resin.

[0012] <2> The structure according to <1>, wherein the nitrogen-containing phenol novolac resin includes a structural unit derived from a triazine compound.

[0013] <3> The structure according to <1> or <2>, wherein the nitrogen-containing phenol novolac resin includes a structural unit derived from melamine.

[0014] <4> The structure according to any one of <1> to <3>, wherein the resin member includes a cured product of a thermosetting resin.

[0015] <5> The structure according to <4>, wherein the thermosetting resin includes an epoxy resin.

[0016] <6> An electronic component device including the structure according to any one of <1> to <5>.

[0017] <7> A method for manufacturing a structure, comprising: preparing a resin member; and disposing a metal film on a surface of the resin member, wherein the resin member comprises a cured product of an epoxy resin and a hardener, and the hardener comprises a nitrogen-containing phenol novolac resin.

[0018] <8> The method for producing a structure according to <7>, further comprising selecting the resin member based on information obtained by an evaluation method including the following (A), (B), and (C).

[0019] (A) A test piece including a resin member and a metal film disposed on the surface of the resin member is prepared.

[0020] (B) As pretreatment of the test piece, the test piece is kept at 60°C to 100°C and at a relative humidity of 60% to 100% for 15 hours or more, and the test piece is heated at a maximum temperature of 200°C or more.

[0021] (C) Using the pretreated test piece, a metal film peeling test was performed.

[0022] Effects of the Invention

[0023] According to one embodiment of the present disclosure, there is provided a structure having excellent adhesion between a resin component and a metal film disposed on the surface thereof, and an electronic component device including the structure. According to another embodiment of the present disclosure, there is provided a method for manufacturing a structure having excellent adhesion between a resin component and a metal film disposed on the surface thereof. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] none DETAILED DESCRIPTION

[0025] In the present disclosure, the term "process" includes processes that are independent of other processes and processes that cannot be clearly distinguished from other processes as long as the purpose of the process is achieved.

[0026] In the present disclosure, in a numerical range represented by “to”, numerical values ​​described before and after including “to” are respectively regarded as the minimum value and the maximum value.

[0027] In the numerical range recorded in stages in the present disclosure, the upper limit or lower limit recorded in one numerical range may also be replaced by the upper limit or lower limit of the numerical range recorded in other stages. In addition, in the numerical range recorded in the present disclosure, the upper limit or lower limit of the numerical range may also be replaced by the value shown in the embodiment.

[0028] In the present disclosure, each component may include a plurality of corresponding substances. When a plurality of substances corresponding to each component are present in the composition, unless otherwise specified, the content or content of each component refers to the total content or content of the plurality of substances present in the composition.

[0029] In the present disclosure, particles corresponding to each component may include multiple types. When multiple types of particles corresponding to each component are present in the composition, the particle size of each component refers to the value for the mixture of the multiple types of particles present in the composition unless otherwise specified.

[0030] <Structure>

[0031] The structure disclosed herein is a structure including a resin member and a metal film disposed on a surface of the resin member, wherein the resin member includes a cured product of an epoxy resin and a curing agent, and the curing agent includes a nitrogen-containing phenol novolac resin.

[0032] In the structure including the above structure, the resin member has excellent adhesion to the metal film disposed on the surface thereof. The reason for this is considered to be that the resin member includes a cured product of an epoxy resin and a hardener and includes a nitrogen-containing phenol novolac resin as a hardener, which acts to improve the adhesion of the surface of the resin member to the metal film, and as a result, the decrease in the adhesion between the resin member and the metal film is suppressed.

[0033] (metal film)

[0034] The material of the metal film disposed on the surface of the resin member is not particularly limited, and examples thereof include copper, silver, iron, nickel, aluminum, titanium, vanadium, chromium, and alloys containing these metals.

[0035] The thickness of the metal film is not particularly limited and can be selected from the range of 10 nm to 1000 μm, for example.

[0036] (Epoxy resin)

[0037] The epoxy resin used in the cured product of the epoxy resin and the hardener is not particularly limited.

[0038] Specific examples of epoxy resins include: novolac-type epoxy resins (phenol novolac-type epoxy resins, o-cresol novolac-type epoxy resins, etc.) obtained by condensing or co-condensing at least one phenolic compound selected from the group consisting of phenolic compounds such as phenol, cresol, xylenol, resorcinol, catechol, bisphenol A, bisphenol F, and naphthol compounds such as α-naphthol, β-naphthol, and dihydroxynaphthalene with an aliphatic aldehyde compound such as formaldehyde, acetaldehyde, and propionaldehyde under an acidic catalyst to obtain a novolac resin, and then epoxidizing the novolac resin; and triphenylmethane-type phenol resins obtained by condensing or co-condensing the phenolic compound with an aromatic aldehyde compound such as benzaldehyde and salicylaldehyde under an acidic catalyst, and then epoxidizing the triphenylmethane-type phenol resins. triphenylmethane epoxy resin obtained by epoxidizing a phenol resin; a copolymerized epoxy resin obtained by epoxidizing a novolac resin obtained by co-condensing the phenol compound and the naphthol compound with an aldehyde compound under an acidic catalyst; a diphenylmethane epoxy resin as a diglycidyl ether of bisphenol A, bisphenol F, etc.; a biphenyl epoxy resin as a diglycidyl ether of an alkyl-substituted or unsubstituted biphenol; a styrene epoxy resin as a diglycidyl ether of a styrene-based phenol compound; an epoxy resin containing sulfur atoms as a diglycidyl ether of bisphenol S, etc.; an epoxy resin as a glycidyl ether of alcohols such as butanediol, polyethylene glycol, and polypropylene glycol; an epoxy resin as a diglycidyl ether of phthalic acid, isophthalic acid, glycidyl ester epoxy resins of glycidyl esters of polycarboxylic acid compounds such as phthalic acid and tetrahydrophthalic acid; glycidylamine epoxy resins obtained by replacing the active hydrogen bonded to the nitrogen atom of aniline, diaminodiphenylmethane, isocyanuric acid, etc. with a glycidyl group; dicyclopentadiene epoxy resins obtained by epoxidizing a co-condensation resin of dicyclopentadiene and a phenol compound; alicyclic epoxy resins such as diepoxy vinylcyclohexene, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, 2-(3,4-epoxy)cyclohexyl-5,5-spiro(3,4-epoxy)cyclohexane-m-dioxane, etc. obtained by epoxidizing an olefin bond in the molecule; glycidyl ethers as p-xylene-modified phenol resins p-xylene modified epoxy resin; meta-xylene modified epoxy resin as glycidyl ether of meta-xylene modified phenol resin; terpene modified epoxy resin as glycidyl ether of terpene modified phenol resin; dicyclopentadiene modified epoxy resin as glycidyl ether of dicyclopentadiene modified phenol resin; cyclopentadiene modified epoxy resin as glycidyl ether of cyclopentadiene modified phenol resin; polycyclic aromatic ring modified epoxy resin as glycidyl ether of polycyclic aromatic ring modified phenol resin; naphthalene type epoxy resin as glycidyl ether of phenol resin containing naphthalene ring; halogenated phenol novolac type epoxy resin; hydroquinone type epoxy resin; trimethylolpropane type epoxy resin; linear aliphatic epoxy resin obtained by oxidizing olefin bonds using peracids such as peracetic acid;Aralkyl epoxy resins obtained by epoxidizing aralkyl phenol resins such as phenol aralkyl phenol resins, biphenyl aralkyl phenol resins, and naphthol aralkyl phenol resins. Furthermore, epoxides of acrylic resins and the like can also be cited as epoxy resins. These epoxy resins can be used alone or in combination of two or more. ;

[0039] From the viewpoint of heat resistance of the resin member, the epoxy resin is preferably a triphenylmethane epoxy resin, a biphenyl aralkyl epoxy resin, a naphthalene aralkyl epoxy resin, or a novolac epoxy resin.

[0040] The epoxy equivalent (molecular weight / number of epoxy groups) of the epoxy resin is not particularly limited, but is preferably 100 g / eq to 1000 g / eq, more preferably 150 g / eq to 500 g / eq, from the viewpoint of balancing various properties such as moldability, reflow resistance, and electrical reliability.

[0041] The epoxy equivalent of the epoxy resin is defined as a value measured by a method in accordance with Japanese Industrial Standards (JIS) K 7236:2009.

[0042] When the epoxy resin is solid, the softening point or melting point is not particularly limited, but is preferably 40° C. to 180° C. from the viewpoint of moldability and reflow resistance, and more preferably 50° C. to 130° C. from the viewpoint of workability.

[0043] The melting point or softening point of the epoxy resin is defined as a value measured by differential scanning calorimetry (DSC) or a method (ring and ball method) in accordance with JIS K 7234: 1986.

[0044] When the resin member contains epoxy resin, the content is preferably 0.5% by mass to 50% by mass, more preferably 2% by mass to 30% by mass, from the viewpoints of strength, fluidity, heat resistance, moldability, and the like.

[0045] (Nitrogen-containing phenol novolac resin)

[0046] Examples of the nitrogen-containing phenol novolac resin used for the cured product of the epoxy resin and the curing agent include phenol novolac resins containing a structural unit derived from a triazine compound.

[0047] Examples of the triazine compound include 1,3,5-triazine, 1,2,4-triazine, 1,2,3-triazine, and derivatives thereof.

[0048] Examples of the derivatives of the triazine compound include triazine compounds having a primary amino group (—NH 2 ) bonded to a triazine ring.

[0049] Among the triazine compounds, 1,3,5-triazine and its derivatives are preferred, melamine and guanamine are more preferred, and melamine is further preferred.

[0050] Examples of the nitrogen-containing phenol novolac resin containing a structural unit derived from melamine include a phenol novolac resin represented by the following formula (1).

[0051] The values ​​of m and n in formula (1) refer to the number of structural units. m and n are each independently selected from the range of 1 to 100, for example.

[0052] [Chemistry 1]

[0053]

[0054] From the viewpoint of improving the adhesion of the resin member to the metal film, the proportion of the nitrogen-containing phenol novolac resin in the entire material of the resin member is preferably 0.1 mass % or more, more preferably 0.2 mass % or more, and even more preferably 0.3 mass % or more.

[0055] The proportion of the nitrogen-containing phenol novolac resin in the entire material of the resin member is preferably 10% by mass or less, more preferably 5% by mass or less, and still more preferably 1% by mass or less, of the entire resin member.

[0056] The hardener used in the hardened product of the epoxy resin and the hardener may be only the nitrogen-containing phenol novolac resin or a combination of the nitrogen-containing phenol novolac resin and other hardeners.

[0057] From the viewpoint of improving the adhesion of the resin member to the metal film, the proportion of the nitrogen-containing phenol novolac resin in the entire hardener is preferably 1 mass % or more, more preferably 2 mass % or more, and even more preferably 5 mass % or more.

[0058] The proportion of the nitrogen-containing phenol novolac resin in the entire hardener is preferably 30% by mass or less, more preferably 20% by mass or less, and still more preferably 10% by mass or less, of the entire hardener.

[0059] Specific examples of hardeners other than the nitrogen-containing phenol novolac resin (other hardeners) include phenol hardeners, amine hardeners, acid anhydride hardeners, polythiol hardeners, polyaminoamide hardeners, isocyanate hardeners, blocked isocyanate hardeners, and active ester compounds. Among these, phenol hardeners are preferred. The hardeners may be used alone or in combination of two or more.

[0060] Specific examples of the phenol curing agent include: polyphenol compounds such as resorcinol, catechol, bisphenol A, bisphenol F, and substituted or unsubstituted biphenols; novolac-type phenol resins obtained by condensing or co-condensing at least one phenolic compound selected from the group consisting of phenol compounds such as phenol, cresol, xylenol, resorcinol, catechol, bisphenol A, bisphenol F, phenylphenol, aminophenol, and naphthol compounds such as α-naphthol, β-naphthol, and dihydroxynaphthalene with an aldehyde compound such as formaldehyde, acetaldehyde, and propionaldehyde in the presence of an acid catalyst; phenol aralkyl-type phenol resins, biphenyl aralkyl-type phenol resins, Aralkyl phenol resins such as naphthol aralkyl phenol resins; p-xylene-modified phenol resins and m-xylene-modified phenol resins; melamine-modified phenol resins; terpene-modified phenol resins; dicyclopentadiene-type phenol resins and dicyclopentadiene-type naphthol resins synthesized by copolymerizing the above-mentioned phenolic compounds with dicyclopentadiene; cyclopentadiene-modified phenol resins; polycyclic aromatic ring-modified phenol resins; biphenyl-type phenol resins; triphenylmethane-type phenol resins obtained by condensing or co-condensing the above-mentioned phenolic compounds with aromatic aldehyde compounds such as benzaldehyde and salicylaldehyde under an acidic catalyst; phenol resins obtained by copolymerizing two or more of these, etc. These phenol curing agents may be used alone or in combination of two or more.

[0061] From the viewpoint of heat resistance of the resin member, as other curing agents, triphenylmethane type phenol resins, biphenyl aralkyl type phenol resins, naphthalene aralkyl type phenol resins, and novolac type phenol resins are preferred.

[0062] When the curing agent is solid, the softening point or melting point thereof is not particularly limited, but is preferably 40° C. to 180° C. from the viewpoint of formability and reflow resistance, and more preferably 50° C. to 130° C. from the viewpoint of workability.

[0063] The melting point or softening point of the curing agent is set to a value measured in the same manner as the melting point or softening point of the epoxy resin.

[0064] The equivalent ratio of epoxy resin to hardener, i.e., the ratio of the number of functional groups in the hardener to the number of functional groups in the epoxy resin (number of functional groups in the hardener / number of functional groups in the epoxy resin) is not particularly limited. From the viewpoint of suppressing the respective unreacted components to a small extent, it is preferably set in the range of 0.5 to 2.0, and more preferably in the range of 0.6 to 1.3. From the viewpoint of formability and reflow resistance, it is further preferably set in the range of 0.8 to 1.2.

[0065] (hardening accelerator)

[0066] The resin member may further contain a hardening accelerator.

[0067] The type of hardening accelerator is not particularly limited, and examples thereof include diazabicycloolefins such as 1,5-diazabicyclo[4.3.0]nonene-5 (DBN), 1,8-diazabicyclo[5.4.0]undecene-7 (DBU), cyclic amidine compounds such as 2-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, and 2-heptadecylimidazole; derivatives of the cyclic amidine compounds; phenol novolacs of the cyclic amidine compounds or their derivatives; Lacquer salts; compounds with intramolecular polarization formed by adding maleic anhydride, 1,4-benzoquinone, 2,5-toluoquinone, 1,4-naphthoquinone, 2,3-dimethylbenzoquinone, 2,6-dimethylbenzoquinone, 2,3-dimethoxy-5-methyl-1,4-benzoquinone, 2,3-dimethoxy-1,4-benzoquinone, phenyl-1,4-benzoquinone and other quinone compounds, compounds with π bonds such as diazonium methane, etc.; cyclic amidinium compounds such as tetraphenylborate of DBU, tetraphenylborate of DBN, tetraphenylborate of 2-ethyl-4-methylimidazole, and tetraphenylborate of N-methylmorpholine; pyridine, triethylamine, triethylenediamine, benzyldimethylamine, tri Tertiary amine compounds such as ethanolamine, dimethylaminoethanol, and tris(dimethylaminomethyl)phenol; derivatives of the tertiary amine compounds; ammonium salt compounds such as tetra-n-butylammonium acetate, tetra-n-butylammonium phosphate, tetraethylammonium acetate, tetra-n-hexylammonium benzoate, and tetrapropylammonium hydroxide; primary phosphines such as ethylphosphine and phenylphosphine, secondary phosphines such as dimethylphosphine and diphenylphosphine, triphenylphosphine, diphenyl(p-toluene)phosphine, tri(alkylphenyl)phosphine, tri(alkoxyphenyl)phosphine, tri(alkylalkoxyphenyl)phosphine, tri(dialkylphenyl)phosphine, tri(trialkylphenyl)phosphine, tri(tetraalkylphenyl)phosphine, tri(dialkoxyphenyl)phosphine, tri(trialkoxyphenyl)phosphine, tri(tetraalkoxyphenyl)phosphine Organic phosphines such as tertiary phosphines such as trialkylphosphine (tributylphosphine, etc.), dialkylarylphosphine, alkyldiarylphosphine, trinaphthylphosphine, tri(benzyl)phosphine, etc.; phosphine compounds such as complexes of the organic phosphine and organic boron; compounds with intramolecular polarization formed by adding maleic anhydride, 1,4-benzoquinone, 2,5-toluoquinone, 1,4-naphthoquinone, 2,3-dimethylbenzoquinone, 2,6-dimethylbenzoquinone, 2,3-dimethoxy-5-methyl-1,4-benzoquinone, 2,3-dimethoxy-1,4-benzoquinone, phenyl-1,4-benzoquinone, anthraquinone, compounds having π bonds such as diazonophenylmethane, etc. to the organic phosphine or the phosphine compound;The organic phosphine or the phosphine compound is reacted with 4-bromophenol, 3-bromophenol, 2-bromophenol, 4-chlorophenol, 3-chlorophenol, 2-chlorophenol, 4-iodophenol, 3-iodophenol, 2-iodophenol, 4-bromo-2-methylphenol, 4-bromo-3-methylphenol, 4-bromo-2,6-dimethylphenol, 4-bromo-3,5-dimethylphenol, 4-bromo-2,6-di-tert-butylphenol, 4-chloro-1-naphthol, 1 -bromo-2-naphthol, 6-bromo-2-naphthol, 4-bromo-4'-hydroxybiphenyl and other halogenated phenol compounds reacted and then dehydrohalogenated; tetraphenylphosphonium and other tetrasubstituted phosphonium, tetraphenyl phosphonium tetra-p-toluene borate and other tetrasubstituted phosphonium tetraphenyl borate, tetrasubstituted phosphonium and phenol compound salts and other tetrasubstituted phosphonium compounds; phosphobetaine compounds; adducts of phosphonium compounds and silane compounds, etc. Among them, triphenylphosphine and adducts of triphenylphosphine and quinone compounds are preferred. ;

[0068] The hardening accelerator may be used alone or in combination of two or more.

[0069] The amount of the hardening accelerator contained in the resin member is preferably 0.1 to 30 parts by mass, and more preferably 1 to 15 parts by mass, relative to 100 parts by mass of the resin component (for example, the total amount of the epoxy resin and the hardener). If the amount of the hardening accelerator is 0.1 parts by mass or more relative to 100 parts by mass of the resin component, there is a tendency to cure well in a short time. If the amount of the hardening accelerator is 30 parts by mass or less relative to 100 parts by mass of the resin component, there is a tendency to obtain a good hardened material with a curing speed that is not too fast.

[0070] (Filling material)

[0071] The resin component may also contain a filler. The type of filler is not particularly limited. Specifically, inorganic materials such as silica such as fused silica and crystalline silica, glass, alumina, talc, clay, and mica may be cited. Inorganic fillers having a flame retardant effect may also be used. Examples of inorganic fillers having a flame retardant effect include composite metal hydroxides such as aluminum hydroxide, magnesium hydroxide, composite hydroxides of magnesium and zinc, and zinc borate.

[0072] In the inorganic filler, from the viewpoint of reducing the linear expansion coefficient, preferably silicon dioxide, from the viewpoint of high thermal conductivity, preferably aluminum oxide. The inorganic filler can be used alone or in combination of two or more. As the form of the inorganic filler, powder, beads, fibers, etc., which are sphericalized powders, can be cited.

[0073] The volume average particle size of the filler contained in the resin member is preferably 10 μm or less, preferably 1 μm to 8 μm, and more preferably 2 μm to 6 μm.

[0074] The maximum particle size of the filler contained in the resin member is preferably 50 μm or less, more preferably 30 μm or less.

[0075] The resin component may also include a filler having a volume average particle size of 0.1 μm or less. When the resin component includes a filler having a volume average particle size of 0.1 μm or less, the content thereof is preferably 10% by mass or less of the entire filler, more preferably 5% by mass or less, and further preferably 3% by mass or less. The content may be 0.1% by mass or more of the entire filler.

[0076] In the present disclosure, the volume average particle size of the filler is the particle size (D50) at which the accumulation from the smaller diameter side in the volume-based particle size distribution obtained using a laser diffraction / scattering particle size distribution measuring apparatus (eg, LA920, manufactured by Horiba, Ltd.) becomes 50%.

[0077] When the filler is contained in the resin member, the volume average particle size of the filler taken out from the resin member by thermal decomposition, melting, or the like may be measured.

[0078] The content of the filler contained in the resin component is not particularly limited. From the perspective of fluidity and strength, it is preferably 30% to 90% by volume of the entire resin component, more preferably 35% to 80% by volume, and further preferably 50% to 80% by volume. If the content of the filler is more than 30% by volume of the entire resin component, there is a tendency that the thermal expansion coefficient, thermal conductivity, elastic coefficient and other characteristics of the cured product are further improved. If the content of the filler is less than 90% by volume of the entire resin component, there is a tendency that the viscosity of the material of the resin component is suppressed, the fluidity is further improved, and the formability becomes better.

[0079] (Silane compound)

[0080] The resin member may further contain a silane compound.

[0081] Specific examples of the silane compound include dimethoxydiphenylsilane, vinyl trichlorosilane, vinyl triethoxysilane, vinyl tri(β-methoxyethoxy)silane, γ-methacryloxypropyl trimethoxysilane, β-(3,4-epoxycyclohexyl)ethyl trimethoxysilane, γ-glycidoxypropyl trimethoxysilane, vinyl triacetoxysilane, γ-mercaptopropyl trimethoxysilane, N-phenyl-γ-aminopropyl trimethoxysilane, γ-aminopropyl triethoxysilane, γ-[bis(β-hydroxyethyl)]aminopropyl triethoxysilane, Silane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, γ-(β-aminoethyl)aminopropyldimethoxymethylsilane, N-(trimethoxysilylpropyl)ethylenediamine, N-(dimethoxymethylsilylisopropyl)ethylenediamine, methyltrimethoxysilane, methyltriethoxysilane, N-β-(N-vinylbenzylaminoethyl)-γ-aminopropyltrimethoxysilane, γ-chloropropyltrimethoxysilane, hexamethyldisilane, γ-phenylaminopropyltrimethoxysilane, vinyltrimethoxysilane and γ-mercaptopropylmethyldimethoxysilane. The silane compound may be used alone or in combination of two or more.

[0082] When the resin member contains a silane compound, the content of the silane compound is preferably 0.1 to 3% by mass relative to the entire resin member, or preferably 0.05 to 10 parts by mass, more preferably 0.1 to 8 parts by mass relative to 100 parts by mass of the filler contained in the resin member.

[0083] (Colorant)

[0084] The resin member may also contain a colorant. As the colorant, known colorants such as carbon black, organic dyes, organic pigments, titanium oxide, red lead, and iron oxide may be cited. The content of the colorant may be appropriately selected according to the purpose of the structure, etc. The colorant may be used alone or in combination of two or more.

[0085] (Ion Exchanger)

[0086] The resin member may also contain an ion exchanger. For example, when the structure is used as an electronic component device with components installed therein, an ion exchanger may be contained from the viewpoint of improving the moisture resistance and high temperature storage characteristics of the electronic component device. As ion exchangers, hydrotalcite compounds and hydroxides containing at least one element selected from the group consisting of magnesium, aluminum, titanium, zirconium and bismuth can be listed. The ion exchangers may be used alone or in combination of two or more. Among them, the hydrotalcite represented by the following general formula (A) is preferred.

[0087] Mg (1-X) Al X(OH)2(CO3) X / 2 ·mH2O……(A)

[0088] (0<X≦0.5, m is a positive number)

[0089] (Flame Retardant)

[0090] The resin member may also contain a flame retardant. The flame retardant is not particularly limited, and previously known ones can be used. Specifically, organic compounds or inorganic compounds containing halogen atoms, antimony atoms, nitrogen atoms or phosphorus atoms, metal hydroxides, etc. can be mentioned. The flame retardant can be used alone or in combination of two or more.

[0091] (wax)

[0092] The resin member may also contain wax. Specific examples of the wax include polyolefin waxes such as oxidized polyethylene wax and non-oxidized polyethylene wax, plant waxes such as carnauba wax, mineral waxes such as montan wax, petroleum waxes such as paraffin wax and microcrystalline wax, higher fatty acids such as stearic acid or their salts, etc. The wax contained in the resin member may be only one type or two or more types.

[0093] <Electronic components and devices>

[0094] The electronic component device of the present disclosure includes the above-mentioned structure.

[0095] The structure included in the electronic component device of the present disclosure has excellent adhesion between the resin member and the metal film disposed on the surface thereof. Therefore, the electronic component device of the present disclosure can continuously achieve excellent electromagnetic interference suppression effect.

[0096] The electronic component device of the present disclosure may include, for example, a supporting member, an element disposed on the supporting member, a resin member disposed around the element, and a metal film disposed on a surface of the resin member.

[0097] Examples of electronic component devices include devices in which components (active components such as semiconductor chips, transistors, diodes, thyristors, etc., passive components such as capacitors, resistors, coils, etc.) are mounted on supporting members such as lead frames, conveyor tapes with completed wiring, wiring boards, glass, silicon wafers, organic substrates, etc., and the periphery of the components are sealed with resin members.

[0098] More specifically, there can be cited general resin-sealed integrated circuits (ICs) such as dual inline packages (DIP), plastic leaded chip carriers (PLCC), quad flat packages (QFP), small outline packages (SOP), small outline J-lead packages (SOJ), thin small outline packages (TSOP), and thin quad flat packages (TQFP), which have a structure in which a component is fixed to a lead frame and a terminal portion of the component such as a bonding pad is connected to a lead portion by wire bonding, bumps, etc., and then sealed with a resin member; a tape carrier package (TCP), which has a structure in which a component connected to a conveying tape by a bump is sealed with a resin member; a chip on a lead frame (Chip On) package (Chip On) package (Chip On) package (Chip On) package (Chip On) package (Chip On) package (Chip On) package (Chip On) package (Chip On) package (Chip On) package (Chip On) package (Chip On) package (Chip On) package (Chip On) package (Chip On) package (Chip On) package (Chip On) package (Chip On) package Board (COB) modules, hybrid ICs, multi-chip modules, etc., which have a structure in which a component connected to wiring formed on a supporting member by wire bonding, flip chip bonding, welding, etc. is sealed with a resin member; a ball grid array (BGA), chip size package (CSP), multi-chip package (MCP), etc., which have a structure in which a component is mounted on the surface of a supporting member having terminals for connecting to a wiring board formed on the back side, and after the component is connected to the wiring formed on the supporting member by bumps or wire bonding, the component is sealed with a resin member.

[0099] <Method for manufacturing structure>

[0100] The method for manufacturing a structured body disclosed herein is a method for manufacturing a structured body, comprising: a step of preparing a resin member; and a step of disposing a metal film on a surface of the resin member, wherein the resin member contains wax.

[0101] In the method disclosed herein, a metal film is formed on the surface of a resin member in a solid state. Therefore, for example, compared with a case where a fluid material such as an uncured thermoplastic resin is brought into contact with a metal member and then the material is cured to produce a structure, sufficient adhesion between the resin member and the metal film may not be obtained.

[0102] In the method disclosed herein, the resin member includes a cured product of an epoxy resin and a hardener and includes a nitrogen-containing phenol novolac resin as a hardener, which acts to improve the adhesion of the surface of the resin member to the metal film. As a result, it is believed that the decrease in the adhesion between the resin member and the metal film is suppressed.

[0103] The method for obtaining the resin member by the method disclosed herein is not particularly limited, and can be selected according to the components contained in the resin member and the like.

[0104] For example, the resin member may be a member obtained by curing a material containing a thermosetting resin.

[0105] Specific examples of a method for curing a material containing a thermosetting resin include a compression molding method, an injection molding method, and a transfer molding method.

[0106] The material containing the thermosetting resin before curing may be either liquid or solid.

[0107] There is no particular limitation on the method of disposing the metal film on the surface of the resin member.

[0108] For example, methods such as sputtering, vapor deposition, plating, and paste coating can be mentioned.

[0109] The material of the metal film is not particularly limited, and examples thereof include copper, silver, iron, nickel, aluminum, titanium, vanadium, chromium, and alloys containing these metals.

[0110] The thickness of the metal film is not particularly limited and can be selected from the range of 10 nm to 1000 μm, for example.

[0111] In the method of the present disclosure, the metal film may be disposed on the entire surface of the resin member, or may be disposed on a portion of the surface of the resin member.

[0112] The method of the present disclosure may further include selecting a resin member used in the structure based on information obtained by an evaluation method including the following (A), (B), and (C).

[0113] (A) A test piece including a resin member and a metal film disposed on the surface of the resin member is prepared.

[0114] (B) As pretreatment of the test piece, the test piece is kept at 60°C to 100°C and at a relative humidity of 60% to 100% for 15 hours or more, and the test piece is heated at a maximum temperature of 200°C or more.

[0115] (C) Using the pretreated test piece, a metal film peeling test was performed.

[0116] By selecting the resin member used for the structure based on the information obtained by the evaluation method including (A), (B), and (C), a structure having excellent adhesion can be efficiently produced.

[0117] The method for preparing the test piece having the resin member and the metal film disposed on the surface of the resin member is not particularly limited, and for example, a method according to the method for producing the structure disclosed in the present invention can be selected.

[0118] In the pretreatment of the test piece, the test piece is kept in an environment of 60°C to 100°C and a relative humidity of 60% to 100% for more than 15 hours (hereinafter also referred to as moisture absorption treatment), and the test piece is heated under the condition that the maximum reached temperature becomes 200°C or more (hereinafter also referred to as heating treatment).

[0119] In the moisture absorption treatment, the test piece is kept in an environment of 60° C. to 100° C. and a relative humidity of 60% to 100% for 15 hours or more.

[0120] The temperature of the moisture absorption treatment is not particularly limited as long as it is within a range of 60°C to 100°C, and may be 85°C, for example.

[0121] The relative humidity of the moisture absorption treatment is not particularly limited as long as it is within the range of 60% to 100%, and may be, for example, 85%.

[0122] The time of the moisture absorption treatment is not particularly limited as long as it is 15 hours or longer, and may be, for example, 15 to 200 hours, or 24 hours.

[0123] In the heat treatment, the test piece was heated under the condition that the maximum reaching temperature became 200° C. or higher.

[0124] The maximum temperature reached in the heat treatment is not particularly limited as long as it is 200°C or higher, and may be, for example, 200°C to 300°C, or 260°C.

[0125] The heat treatment may be performed in the air or in an inert atmosphere such as nitrogen. When the metal film includes an easily oxidizable metal such as copper, the heat treatment is preferably performed in an inert atmosphere.

[0126] The number of times of heat treatment is not particularly limited, but from the viewpoint of evaluation accuracy, heat treatment is preferably performed twice or more, and more preferably performed three times or more.

[0127] The method for conducting the peel test of the test piece is not particularly limited, and examples thereof include a cross cut test, a peel test, a scratch test, and a grid method test.

[0128] The criteria for evaluating the results obtained in the peel test are not particularly limited, and can be set so as to achieve desired evaluation accuracy.

[0129] Example

[0130] Hereinafter, the present invention will be specifically described by way of examples, but the scope of the present invention is not limited to these examples.

[0131] <Preparation of test pieces>

[0132] Using the composition containing the materials shown in Table 1, a test piece in which a metal film was arranged on the surface of a resin member was prepared.

[0133] Specifically, a composition containing the materials shown in Table 1 was formed on a substrate at a mold temperature of 175°C and a molding time of 120 seconds. Then, the substrate was peeled off and post-cured at 175°C for 5 hours to obtain a cured product of 235 mm×65 mm×0.7 mm. A copper film (thickness: 500 μm) was formed on one of the main surfaces and the side surface of the obtained cured product by sputtering to obtain a test piece.

[0134] <Evaluation of Adhesion>

[0135] The test piece was subjected to moisture absorption treatment in an environment of 85° C. and 85% relative humidity for 24 hours, and then subjected to heat treatment three times in a nitrogen atmosphere at a maximum temperature of 260° C.

[0136] The test piece after the above treatment was subjected to a cross-cut test in accordance with JIS K 5600. The number N was set to 3.

[0137] Specifically, cuts were made at 1 mm intervals on the metal film of the test piece to form 25 (5 vertical × 5 horizontal) grids, and adhesive tape was attached thereto. After the adhesive tape was attached, it was torn off at an angle of 60° within 0.5 to 1.0 seconds within 5 minutes.

[0138] The adhesion of the metal film was evaluated based on the ratio (area basis) of the metal film remaining after the tape was removed according to the following criteria.

[0139] 1: Less than 5%

[0140] 2: 5% or more but less than 15%

[0141] 3: 15% or more but less than 35%

[0142] 4: 35% or more but less than 65%

[0143] 5: More than 65%

[0144] <Evaluation of liquidity>

[0145] The composition containing the materials shown in Table 1 was molded using a spiral flow measurement mold in accordance with EMMI-1-66 under the conditions of a molding pressure of 6.9 MPa, a curing time of 120 seconds, and a molding temperature of 180°C, and the flow distance (cm) was determined. The results (Spiral Flow (SF)) are shown in Table 1.

[0146] <Evaluation of flexural modulus, flexural strength, and elongation at break>

[0147] The composition containing the materials shown in Table 1 was formed under the conditions of a forming pressure of 6.9 MPa, a curing time of 120 seconds, and a forming temperature of 175°C to produce a test piece of 70 mm × 10 mm × 3 mm. A three-point support type bending test according to JIS-K-6911 (2006) was performed at 25°C using Tensilon of A&D Company to obtain the bending elastic coefficient, bending strength, and elongation at break of the test piece. The results are shown in Table 1. In addition, the bending elastic coefficient E is defined by the following formula.

[0148] In the following formula, E is the bending elastic coefficient (MPa), P is the value of the dynamometer (N), y is the displacement (mm), l is the span = 48 mm, w is the test piece width = 10 mm, and h is the test piece thickness = 3 mm.

[0149] [Formula 1]

[0150]

[0151] [Table 1]

[0152] Comparative Example 1 Example 1 Epoxy resin 1 50 50 Epoxy Resin 2 50 50 Hardener 1 59 54.8 Hardener 2 0 4.67 Hardening accelerator 1.6 1.6 Coupling agent 1 2 2 Coupling agent 2 2 2 Colorants 3.5 3.5 Filling material 1 805 807 Filling material 2 43 43 Filling material 3 7 7 Total (parts by mass) 1023.1 1025.6 Filler (volume %) 72.5 72.5 Tightness 5 3 SF(cm) 235 232 Elongation at break (%) 68% 91% Bending elastic modulus (GPa) 20.2 20.6 Bending strength(MPa) 121 143

[0153] The details of the materials shown in Table 1 are as follows.

[0154] Epoxy resin 1···Biphenyl type epoxy resin, epoxy equivalent weight 192

[0155] Epoxy resin 2···Triphenylmethane type epoxy resin, epoxy equivalent weight 169

[0156] Hardener 1···Phenol aralkyl type phenol resin containing no nitrogen atom, hydroxyl equivalent weight 106

[0157] Hardener 2: Phenol novolac resin having a structure represented by formula (1)

[0158] Hardening accelerator···Adduct of triphenylphosphine and p-benzoquinone

[0159] Coupling agent 1···N-phenyl-γ-aminopropyltrimethoxysilane

[0160] Coupling agent 2···γ-glycidyloxypropyltrimethoxysilane

[0161] Colorant···Carbon black

[0162] Filler 1: Fused silica, volume average particle size 15 μm, specific surface area 2.7 m 2 / g

[0163] Filler 2: Fused silica, volume average particle size 0.5 μm, specific surface area 6.3 m 2 / g

[0164] Filler 3: Fused silica, volume average particle size 0.1 μm or less, specific surface area 205 m 2 / g

[0165] As shown in the above results, the test piece of Example 1 using the nitrogen-containing phenol novolac resin as a hardener showed excellent evaluation of the adhesion of the metal film compared with the test piece of Comparative Example 1 not using the nitrogen-containing phenol novolac resin as a hardener.

[0166] The entire contents of the disclosure of Japanese Patent Application No. 2022-188726 are incorporated into this specification by reference.

[0167] All documents, patent applications, and technical specifications described in this specification are cited and incorporated into this specification to the same extent as if each document, patent application, or technical specification was specifically and individually described as being incorporated by reference.

Claims

1. A structure comprising a resin member and a metal film disposed on a surface of the resin member, wherein the resin member comprises a cured product of an epoxy resin and a curing agent, and the curing agent comprises a nitrogen-containing phenol novolac resin.

2. The structure according to claim 1, wherein The nitrogen-containing phenol novolac resin includes a structural unit derived from a triazine compound.

3. The structure according to claim 1, wherein The nitrogen-containing phenol novolac resin includes a structural unit derived from melamine.

4. The structure according to claim 1, wherein: The resin member includes a cured product of a thermosetting resin.

5. The structure according to claim 4, wherein: The thermosetting resin includes epoxy resin. 6 . An electronic component device comprising the structure according to claim 1 .

7. A method for manufacturing a structure, comprising: preparing resin components; A metal film is disposed on the surface of the resin member, and the resin member includes a cured product of an epoxy resin and a curing agent, and the curing agent includes a nitrogen-containing phenol novolac resin.

8. The method for manufacturing a structure according to claim 7, further comprising selecting the resin member based on information obtained by an evaluation method including the following (A), (B), and (C), (A) preparing a test piece having a resin member and a metal film disposed on a surface of the resin member; (B) as pretreatment of the test piece, the test piece is kept in an environment of 60°C to 100°C and a relative humidity of 60% to 100% for 15 hours or more, and the test piece is heated under the condition that the maximum reaching temperature is 200°C or more; (C) Using the pretreated test piece, a metal film peeling test was performed.